The Return : Intertextuality of the Reminiscing of Karelian Evacuees in Finland - Savolainen, Ulla (The Journal of American Folklore, 2017)
In this article, I examine the intertextuality of reminiscence writings of Karelian evacuees in Finland. The main topics of these writings are the two journeys of evacuation from the ceded Karelia to Finland, which writers experienced as chil- dren during and after the Second World War, and journeys back to the region of their childhood, which became possible after the collapse of the Soviet Union. In the case of negotiations surrounding spatiotemporal distance and the creation of bridges between the past and the present, I argue that intertextuality plays a crucial but somewhat underanalyzed role in reminiscing. Peer reviewed